SELF-ADJUSTING DISTRIBUTED CONTROL SYSTEMS - I. M. Pershin; V. A. Nosova; V. V. Tsapleva (Современная наука и инновации)
Distributed control systems are considered that have the ability to change the parameters of a distributed controller depending on changes in the parameters of a distributed object. By nature, the considered adaptive systems belong to the group of selfadjusting systems. The article considers the procedure for the synthesis of an adaptive distributed controller